SIRAH NABAWIYAH DALAM PERSPEKTIF TEORI KEBUTUHAN VERSI DAVID McCLELLAND - Rosidin, Rosidin (STAI Ma'had Aly Al-Hikam Malang, 2015)
Modern technology causes narrowing job opportunities. Condition today, requires creative individuals. Facts show the Prophet as a figure who successfully breaks through the world of work in the midst of all limited. theory of needs was initiated by David McClelland contains three requirements, (the Need for Achievement / N-Ach), (the Need for Affiliation / N-affil) (the Need for Power / N-Pow). Associated with sira Nabawiyah: 1) How the values of N-Ach, N-affil and N-Paw in sirah nabawiyah ?; 2) How is the manifestation of the values of N-Ach, N-affil and N-Pow 'Nabawiyah' in the present context ?; 3) How does character education values of N-Ach, N-affil and N-Pow 'Nabawiyah' in the present context? The results of research were obtained: 1) The values of N-Ach in sirah nabawiyah include prophetic morals at the level of the pre , processes and post-employment; N-affil include prophetic character in the context of a social conscience, obey the norm and give priority to cooperation; whereas N-Pow include related prophetic morals personality and leadership; 2) In the present context, the value of N-Ach, N-affil and N-Pow 'Nabawiyah' includes ethos pious, scientific ethos, ethics and ethos amaliah akhlakiah; 3) Education character N-Ach, N-affil and N-Pow 'Nabawiyah' in the present context is held through educational methods prophetic in three stages: Moral Feeling, Knowing and Moral Moral Moral Doing-Being; with accompanying educational principle in the form of reward-punishment, harmonious relations, interest-talent, edu-tainment, democratization and tiered.